2004
DOI: 10.5032/jae.2004.01062
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Science Teachers Regarding the Integration of Science Into the Agricultural Education Curriculum

Abstract: Science teachers who taught in a high school with an Agricultural Science and Technology Program were the focus of this study to determine their support for integrating science into Agricultural Education Programs. Results indicated that science teachers have responded positively to the call to integrate science into the agricultural education curriculum. The participants agreed that agriculture is an applied science and students are more aware of the science connections and learn more through an integrated cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 15 publications
4
35
0
Order By: Relevance
“…However, teachers in our study perceived horticultural-centered curricula as a means to support only their non-science standards. Others have also found that teachers have missed opportunities to support their teaching using agricultural contexts or themes (Eames-Sheavley, 1994;Warnick, Thompson, & Gunner, 2004). Skelly and Bradley (2000) evaluated elementary teachers' perceptions and use of school gardens and found that few teachers in their study integrated their garden to teach course content.…”
Section: Teachers' Belief That Horticultural Lessons Are Not Science-mentioning
confidence: 99%
“…However, teachers in our study perceived horticultural-centered curricula as a means to support only their non-science standards. Others have also found that teachers have missed opportunities to support their teaching using agricultural contexts or themes (Eames-Sheavley, 1994;Warnick, Thompson, & Gunner, 2004). Skelly and Bradley (2000) evaluated elementary teachers' perceptions and use of school gardens and found that few teachers in their study integrated their garden to teach course content.…”
Section: Teachers' Belief That Horticultural Lessons Are Not Science-mentioning
confidence: 99%
“…It is clear by pre service teacher statements that prior knowledge can have an effect on their ability to integrate core academic courses; identifying a need for scrutiny of how many credit hours of math, science, and English pre service agriculture teachers are required to take. Moreover, justifying the need for evaluation of the core academic classes agricultural education majors are including in their university program plan, corroborating the findings of Warnick et al, (2004) vis-à-vis the effective integration of science and math into their coursework.…”
Section: Conclusion and Recommendationsmentioning
confidence: 57%
“…What is more, those teachers who have developed a higher teacher-efficacy are more likely to utilize a constructivist approach to their teaching, emphasizing inquiry based learning, as well as additional educational strategies targeted at student centered learning (Czerniak, 1990). With the increased push for agriculture teachers to incorporate academic concepts (Myers & Dyer, 2004), teachers have indicated a need for teacher education programs to provide increased content knowledge and pedagogical training (human capital) deemed necessary for the effective emphasis and integration of science and math in the curriculum (Gill, 2009;Warnick et al, 2004), moreover, providing pre-service teachers the opportunity to gain self-assurance and an increased level of efficacy during their residency teaching experience (Robinson, Krysher, Haynes, & Edwards, 2010).…”
mentioning
confidence: 99%
“…Moreover, it could be implied that when student teachers are allowed to teach across the curriculum, their technical skills are enhanced. Recommendations have included pre-service and in-service education for learning how to integrate technical content into the secondary agricultural education curriculum (Edwards & Thompson, 2010;Harris & Birkenholz, 1996;Myers & Dyer, 2004;Parr, Edwards, & Leising, 2009;Warnick, Thompson, & Gummer, 2004;Young, Edwards, & Leising, 2009). Further, recommendations have sought to focus preservice students on the importance of integrating content through cross-curricular instruction (Conroy & Walker, 2000) and developing new models within pre-service teacher education programs to advocate for and solicit integration practices (Kotrlik, Redmann, & Douglas, 2003;Parr et al, 2009;Young et al, 2009).…”
Section: How Oklahoma State University Students Spent Their Time Studmentioning
confidence: 99%
“…How often are instructional technologies used as tools for teaching secondary agricultural education? More emphasis should be placed on instructing pre-service teachers as to the importance of documenting time spent integrating technical content into the agricultural education curriculum (Harris & Birkenholz, 1996;Myers & Dyer, 2004;Parr et al, 2009;Warnick, Thompson, & Gummer, 2004;Young et al, 2009). …”
Section: Recommendations For Further Researchmentioning
confidence: 99%